2008
DOI: 10.1007/s00436-008-0880-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of T cell deficiency on the development of worms and granuloma formation in mice infected with Schistosoma japonicum

Abstract: It is widely accepted that the immune response of the host attacks the parasite and the parasite appears to develop strategies to evade the assault. However, there is increasing evidence that the development of a parasite may be also positively influenced by the immune response of host. In this paper, we explore the effects of T cell deficiency on the development of the worms and granuloma formation in mice infected with cercariae of Schistosoma japonicum. T cell-deficient (nude) mice supported normal parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
4
27
1
Order By: Relevance
“…Secondly, LRG-47 −/− mice produce more IL-10 in the course of Schistosoma japonicum infection or SEA immunization, which has a central role in the pathogenesis of schistosomiasis and restrains the size of hepatic granuloma. Finally, schistosomes as the complex creature might require the host immune signal in the process of development, maturity and spawning (Cheng et al 2008). If the host immune system is Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, LRG-47 −/− mice produce more IL-10 in the course of Schistosoma japonicum infection or SEA immunization, which has a central role in the pathogenesis of schistosomiasis and restrains the size of hepatic granuloma. Finally, schistosomes as the complex creature might require the host immune signal in the process of development, maturity and spawning (Cheng et al 2008). If the host immune system is Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It suggests that depletion of IL-12 may cause an increased production of IL-4 in S. japonicum-infected mice. It has been demonstrated that development of schistosome worms and formation of egg-induced granuloma in host are closely related to host immune factors (Amiri et al 1992;Owhashi et al 1997;Cheng et al 2008). One of our findings was that IL-12 deficiency in mice appeared to not influence the survival of S. japonicum but to benefit development of the worms.…”
Section: Discussionmentioning
confidence: 98%
“…Digital images of each stained worm were obtained using a microscope equipped with a Nikon Coolpix 5400 digital camera, and parasite length was measured from the digital images using "Image-Pro Plus 5.0" software (Cheng et al 2008). …”
Section: Measurement Of Worm Lengthmentioning
confidence: 99%
“…Several experimental studies have indicated that once established the parasites do not have a passive existence in the host. Apart from obtaining nutrients, the parasites rely on cues from the host for reproduction and development (Babayan et al, 2010;Davies et al, 2001;Cheng et al, 2008;Tang et al, 2013;Lamb et al, 2010). Growth and development of schistosomes can be positively influenced by the host immune cells.…”
Section: Establishment In the Hostmentioning
confidence: 99%